Perivascular cerebrospinal fluid inflow matches interstitial fluid efflux in anesthetized rats - Kristian N. Mortensen; Tuomas Lilius; Marko Rosenholm; Björn Sigurðsson; Douglas H. Kelley; Maiken Nedergaard (iScience)
Summary: Waste solutes are cleared from the brain via outflow of interstitial fluid (ISF). Blood-brain barrier (BBB) water secretion and inflow of cerebrospinal fluid (CSF) via perivascular channels have been suggested as potential fluid sources to replace outflowing ISF. To assess the role of CSF inflow in brain clearance, we measured both CSF inflow and ISF outflow in ketamine/dexmedetomidine anesthetized rats. We used magnetic resonance imaging (MRI) and single-photon emission computed tomography (SPECT) to track tracer flows after infusion in CSF or ISF. CSF inflow was estimated at 0.5–0.7 μL g−1 min−1 using either direct observation of perivascular flow or compartment modeling. ISF outflow was estimated at 0.47 ± 0.05 μL g−1 min−1 after intraparenchymal infusion. Our observations indicate that, under the anesthetic condition examined, inflowing CSF is sufficient to replace outflowing ISF, perivascular flow and CSF inflow to interstitium are dominated by convection, and diffusion and convection both contribute to tracer transport within the brain parenchyma.